Learning By Teaching: A Cultural Historical Perspective On A Teacher’s Development - Gordon, Sue; Fittler, Kathleen (Outlines. Critical Practice Studies, 2004)
<span style="font-family: Times; font-size: 12pt; mso-ansi-language: EN-AU; mso-fareast-font-family: ’Times New Roman’; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;" lang="EN-AU">How can teacher development be characterised? In this paper we offer a conceptualisation of teacher development as the enhancement of knowledge and capabilities to function in the activity of a teacher and illustrate with a case study. Our analytic focus is on the development of a science teacher, David, as he engaged in an innovative, collaborative project on learning photonics at a metropolitan secondary school in Australia. Three dimensions of development emerged: technical confidence and competence, pedagogical development and personal agency. We explore the transformative effects of intrapersonal tensions within the teacher’s constitution of his role in the emerging community of enquiry — positioning him in turn as learner, instructor and facilitator. We view the context for David’s actions as a complex and dynamic system and interpret David’s development as arising from his responses to the differences in his emerging roles in the project.